IMPLEMENTATION OF SIMPLE ADDITIVE WEIGHTING (SAW) ALGORITHM IN DECISION SUPPORT SYSTEM FOR DETERMINING WORKING AREA FOR COOPERATIVE - Subhan Hafiz Nanda Ginting; M. Rhifky Wayahdi; Dinur Syahputra (Sean Institute, 2020)
Today, the cooperative in Medan has difficulty in determining the work area for employees. The difficulty in determining the work area of ​​employees is because the number of employees does not meet the needs. In addition, the employees' lack of knowledge about the work area will be a problem. This has resulted in obstruction of the performance of employees at the Medan Cooperative. To overcome this problem, a decision support system is needed that can assist in making decisions to determine the employee's work area. Using the Simple Additive Weighting (SAW) method is expected to help companies to be able to assess and determine employees who meet the criteria and can work for a long time. The Decision Support System for selecting the work area that is currently being designed is the Decision Support System for Determining Work Areas in Cooperatives in Medan Using the Simple Additive Weighting (SAW) Method. Where with this system it can make it easier for companies to place employee work areas based on the area where the employee lives. The system designed can be used for all employees because it is very easy to use, no special computer skills are needed. So that employees can use this system to generate reports about their work area based on residence. Decision support system application designed using the Simple Additive Weighting (SAW) method at the Cooperative in Medan, can determine the work area of ​​employees.